Maternal and neonatal complications in hystrectomy patients with types of abnormal placental adhesion - Seyedeh Azam Pourhoseini; Sara Mirzaeian; Lida Jarahi; Mahdiyeh Arefi (Mashhad University of Medical Sciences, 2021)
Introduction: Abnormal placental adhesion is often associated with severe life-threatening bleeding that requires peri-delivery emergency hysterectomy and can increase the risk of complications such as Disseminated intravascular coagulation, respiratory distress and renal failure for mother. This study was performed with aim to investigate the maternal and neonatal complications in patients with abnormal placental adhesion. Methods: This cross-sectional study was performed on 70 pregnant women with abnormal placental adhesion in the educational hospitals of Mashhad University of Medical Sciences in 2017-2018. Patients with abnormal placental adhesions who were diagnosed through Doppler or MRI and given a clinical diagnosis during cesarean section and then confirmed in pathology results entered the study. Data collection tool was a researcher-made checklist. Based on the pathology sample, the patients were divided into 3 groups of abnormal placental adhesions. Maternal and neonatal complications were evaluated for each group based on the amount and degree of adhesion. Qualitative data were reported as frequency and percentage. Chi-square test was used to compare their frequency distribution. One-way analysis of variance and Kruskal-Wallis tests were used to compare the means of quantitative variables. P<0.05 was considered statistically significant. Results: The most common complication in all three groups was prepartum hemorrhage that the difference between three groups was not significant (p=0.571). There was no significant difference between three forms of adhesion groups in urinary system complications(p=0.294) ,transfusion(p=0.29), neonatal NICU admission and death(p= 0.44).